Implementasi Asta Cita Dalam Kebijakan Pembangunan Daerah di Kecamatan Kairatu Kabuapeten Seram Bagian Barat - Mohamad Arsad Rahawarin; Hendry Selanno (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the implementation of regional development policies in Kairatu District, West Seram Regency, aligned with Asta Cita principles, evidence-based approaches, and local potential. The findings indicate that Asta Cita has been integrated into regional planning documents and translated into district programs through participatory mechanisms. Evidence-based policy implementation relies on statistical data, sectoral reports, and village-level data to ensure alignment with community needs. Local potential, particularly in agriculture, fisheries, and plantations, serves as the foundation for contextual and relevant development policies. Program implementation is supported by performance indicators and the role of district officials as mediators between regency policies and local conditions. Success is driven by governmental commitment, community participation, and institutional synergy, while constraints include limited budgets, infrastructure, human resource capacity, and social participation. The study recommends strengthening officials’ capacity, improving data quality, upgrading infrastructure, and expanding community involvement to achieve more effective and sustainable development.